2011
DOI: 10.4103/2230-973x.85964
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of sustained release bioadhesive tablets of ofloxacin using 32factorial design

Abstract: Background:Oral sustained release gastroretentive dosage forms offer many advantages for drugs having absorption from upper gastrointestinal tract and improve the bioavailability of medications that are characterized by narrow absorption window. The aim of current study was to design sustained release bioadhesive gastroretentive dosage form of ofloxacin.Materials and Methods:A 32 full factorial design was employed to systematically study the drug release profile and bioadhesive strength. Carbopol 934P and HPMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Radiology or X-ray is another alternative technique where a radio-opaque material with the GRDDS is included. This technique has been noted in the evaluation of gastroretentivity, the rate of disintegration of DFs, and their esophageal transit [81]. To diagnose and monitor the GIT, gastroscopy is another commonly used technique.…”
Section: In Vivo Assessment Of Gastroretentive Propertiesmentioning
confidence: 99%
“…Radiology or X-ray is another alternative technique where a radio-opaque material with the GRDDS is included. This technique has been noted in the evaluation of gastroretentivity, the rate of disintegration of DFs, and their esophageal transit [81]. To diagnose and monitor the GIT, gastroscopy is another commonly used technique.…”
Section: In Vivo Assessment Of Gastroretentive Propertiesmentioning
confidence: 99%
“…Among these drugs with NAW is L-DOPA [24], furosemide [25], baclofen [26], riboflavin [27] and para-aminobenzoic acid [28,29]. The prepared formulations could effectively sustain the release of such drugs but the major drawbacks in these formulations these drugs have NAW; therefore prolonging the drug release cannot be sufficient to improve drug bioavailability as these drugs cannot be absorbed after passing the desired part of the absorption [30,31]. In general, drugs which display NAW difficult to be formulated as immediate release DDS or oral controlled release drug delivery system (CRDDS) because of the preparation of these drugs in the form of immediate release dosage forms require frequent use of a dosage form which did not improve patient compliance in addition to side effects related to the rapid release of those drugs, while sustain drug release could prolong the release time which in such cases shows no benefits because only the drug absorbed in a definite segment along the GIT [32].…”
Section: Gastroretentive Drug Delivery Systemsmentioning
confidence: 99%
“…Gangurde HH et al, reported that the detachment force was increased with the increase in polymer concentration after evaluating the sustained release GRDDS tablets of ofloxacin. This could be due to the availability of more adhesive sites and polymer chains for interpenetration with mucin, resulting consequently in the increase of bioadhesive strength 26 . Recently Kar K et al, also demonstrated the similar results and concluded that hydrophilic polymers are the good candidate for preparation of bioadhesive tablet 27 .…”
Section: In-vitro Dissolution Studymentioning
confidence: 99%